Influential determinants of international students' satisfaction in higher education - Daud, Nureezan; Ali, Noor Azman; Jantan, Amer Hamzah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
It has been argued that international students’ satisfaction level is crucial in measuring HEIs performance in the globalized higher education market. However, as satisfaction level is hard to define because it is based on students’ perception and experience, there is a need for HEIs to continually investigate and identify the factors that contribute to students’ satisfaction. Hence, this study seeks to identify the influential determinants of international students’ satisfaction in higher education and to examine the relationships between perception, costs, reputation, lecturers’ expertise, learning environment, facilities and course structure towards international students’ satisfaction. A total of 281 international postgraduate students at public HEI in Malaysia participated in this study. Data of this study was to examine using the Multiple Regression Analysis. Results of the study revealed learning environment factor as the most influential determinant of international students’ satisfaction. Results also proved that except for costs and reputation, other service quality factors namely, perception, lecturers’ expertise, facilities, learning environment, and course structure were found to influence international students’ satisfaction significantly. This study provides insights to HEIs to better design their internationalization strategies and bridge the academic gap by highlighting the importance of continuously improving the learning environment in HEIs to increase international students’ satisfaction.